Pengaruh Red Flags, Training dan Profesionalisme Terhadap Kemampuan Auditor Dalam Mendeteksi Fraud: (Literature Review Audit Investigasi) - Ajeng Putri Wahyuningtyas; Dina Erliana; Machdar Nera Marinda (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This review article examines the influence of red flags, training and expertise on the auditor's ability to detect fraud. This research is a literature study for the investigative audit course which aims to develop hypotheses regarding the influence between variables that can be used for further research.